[P210] Track structure-based corrections for ionization quenching in scintillators exposed to ions. (August 2018) - Christensen, Jeppe Brage; Andersen, Claus E.
Abstract : Purpose: Organic plastic scintillators are attractive for particle therapy dosimetry due to their prompt response and good water-equivalence. However, scintillators exhibit a signal reduction, termed ionization quenching, as they are exposed to radiation with a high linear energy transfer (LET). The semi-empirical Birks model[1] is widely used in solid state dosimetry to correct the signal for quenching but breaks down even for low-energy photons. Furthermore, the Birks model erroneously gives the same correction factor for two different heavy charged particles (HCPs) with the same LET which contradicts experimental observations. We propose a new method, based on track structure theory, to correct for quenching in organic scintillators exposed to HCPs. Methods: The kinetics of excited states in an organic scintillator can be modeled by a general equation derived by Blanc[2] . Birks model is a solution to the equation only if several terms are neglected while the radial energy deposition distribution is unaccounted for. However, we apply track structure theories to distribute the excited states in accordance with energy deposition by secondary electrons, and calculate the resulting luminescence as governed by the Blanc model. Results: The calculated scintillator response is validated against experimental data. The solutions show, that ionization quenching occurs at a time scale corresponding to the characteristic decay time of the scintillator. Additionally, we are able to predict critical fluence-rate thresholds for which the ion tracks at different energies start to overlap and thus enhance the quenching non-linearly. Conclusions: An algorithm, which readily computes quenching correction factors based on the Blanc model for several scintillators, is presented as the open source software package QuenchingKinetics. The software extends the Birks model by taking ion track structures into account and, furthermore, provides information about the temporal structure of quenching and fluence-rate thresholds for ions as a function of energy.